Sexuality of women using oral contraceptives - A L Unanyan; S E Arakelov; L S Polonskaya; V D Morozova; D V Baburin; Yu M Kossovich (IP Berlin A.V., 2014)
Female sexual health is the guarantee of the gynecological illnesses prophylaxis and a key component defining quality of life. Choice of contraception method providing the absence of any unexpected pregnancy risks and fears, as well as high level of freedom in sex and intimate comfort formation holds an important place in harmonization of sexual relations.